(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Cancer is one of the great challenges for the patient and his family, often the family or caregivers suffer from psychological burden. Cancer is a devastating disease that necessitates extensive treatment and ongoing support to aid people physically, emotionally, and financially. Therefore, not only does the sufferer but also his loved ones feel the weight of a cancer diagnosis. Family members typically offer care for a loved one with cancer in addition to professional aid, beginning with the initial diagnosis and continuing through recovery or death. Increased survival rates are the result of significant advancements in therapy, and cancer is now more likely to be viewed as a chronic condition requiring care primarily outside of a hospital. They seem to be more likely to get sick and die, which is a sign of a higher risk for death. Caregiver burden is when a caregiver’s mental or physical health is at risk or when the amount of care, they have to give is more than they can handle. The load seems to be common among family caregivers, but there are not many ways to help them. There are factors that increase the burden on caregivers and thus make it more difficult for their patient to recover, because caregivers are unable to fully comply with them because of the burden.